Exploring the relationship between exercise addiction and intuitive and mindful eating: a pilot study among regular exercisers - Güzel, Rümeysa; Çetin, Neslihan; Seven Avuk, Hande (Edizioni Minerva Medica, 2024)
BACKGROUND: Exercise addiction, characterized by an uncontrollable urge to exercise excessively, poses significant physical, social, and psychological risks. This study aimed to assess the influence of individuals’ intuitive eating behavior and eating mindfulness on exercise addiction levels among regular exercisers. METHODS: A total of 101 individuals engaged in regular exercise, at least three days per week, for one year participated in the study. Sociodemographic information was collected through face-to-face interviews, and participants completed the Exercise Addiction Scale (EAS), Intuitive Eating Scale-2 (IES-2), and the Mindful Eating Questionnaire (MEQ). Additionally, dietary intake was assessed using a 24-hour food consumption record survey form. RESULTS: The average EAS score was 50.71±11.14 points, with 53.5% of participants at risk and 46.5% addicted to exercise. No significant differences were observed in other subscales and total scores of IES-2 and the MEQ across exercise addiction levels (P>0.05). However, body food choice congruence, one of the sub-dimensions of the intuitive eating scale, was found to be significantly higher in individuals with exercise addiction than in those at risk of addiction. Individuals at risk of exercise dependence showed significantly lower average daily intakes of protein, cholesterol, thiamine, niacin, potassium, iron, and magnesium compared to those at an addicted level (P<0.05). CONCLUSIONS: While regular exercise has evident health benefits, it is essential to consider individuals’ attitudes toward nutrition and behavior to mitigate the risk of exercise addiction and associated health issues. This pilot study contributes to the limited literature on exercise addiction, intuitive eating, and eating mindfulness, underscoring the need for further research. © 2024 EDIZIONI MINERVA MEDICA.
Keywords: Eating; Exercise; Mindfulness